Team Game Tournament (TGT)-type cooperative learning model: How does it affect the learning outcomes of football shooting? - Rubiyatno; Perdana, Rahmat Putra; Supriatna, Eka; Yanti, Novi; Suryadi, Didi (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2023)
Football shooting is a technique of kicking the ball towards the goal with the aim of obtaining winning numbers in a match. However, there are still many students who have difficulty shooting in football games. Therefore, it is necessary to have special treatment in order to get satisfactory shooting results in a game. This study aims to prove the effect of the team game tournament (TGT) type cooperative learning model on the learning outcomes of shooting football. In this study, the type of experiment used was a pretest and posttest for one group. The subjects in this study were students of class VIII-A at SMP Negeri 2 in the 2022–2023 academic year. In this study, saturated sampling technique was used, so 31 students were obtained as samples. Data analysis in this study was assisted by using the SPSS Version 26 application. This study obtained a significance value of 0.000 0.05, and based on these results, the team game tournament (TGT) type cooperative learning model has a significant effect on the learning outcomes of basketball shooting. The conclusion is that the TGT type cooperative learning model treatment has a significant effect on shooting learning outcomes, so these results can be applied to improve learning outcomes in shooting football games. The results of this study provide additional references for sports teachers and sports practitioners related to the TGT type cooperative learning model so that this model can be applied in physical education learning, especially the shooting material of soccer games.